ANALYSIS OF THE INFLUENCE OF SERVICE QUALITY AND PRODUCT QUALITY ON WIFI ID CUSTOMER SATISFACTION AT PT. TELKOM INDONESIA REGIONAL 7 - hafry, hasand (Scientium Management Review, 2022)
Abstract This study aims to determine the effect of service quality on customer satisfaction; product quality on customer satisfaction; service quality and product quality on customer satisfaction Wifi Id at PT. Telkom Indonesia Regional 7. This research is a quantitative research with a causal associative approach, that aims to determine the effect of two or more variables. This research conducted at PT. Telkom Indonesia Regional 7, by taking a sample, namely Wifi Id customers, totaling 352 respondents. Data collection techniques using observation techniques, interviews, questionnaires and literature study. The data were analyzed using validity tests, reliability tests and multiple linear regression analysis. The results of the study show that service quality has a positive and significant effect on customer satisfaction. Product quality has a positive and significant effect on customer satisfaction. Service quality and product quality have a positive and significant effect on customer satisfaction at PT. Telkom Indonesia Regional 7.